Kinetic and thermodynamics study of heavy metal ions adsorption from aqueous solution using new resin 8-hydroxyquinoline-furfural-hydroquinone (HQFH). (Journal of the College of Basic Education, 2023)
Used in this study to prepare for the new cross linked polymeradsorption to remove heavy metals(Hg*’,Cd*’,Zn*?,Pb”) in aqueoussolution . Using UV-Visible spectrophotometer technique to determine theamount of adsorption and factors affecting the adsorption of PH and thedistribution coefficient and the effect of temperature and study thethermodynamic functions process. The results showed that the highestamount of adsorption was ion (Zn*), which was 98.9% , Pb**= 80.2%,Cd=75.3% and Hg*=67.9%. The results the thermodynamic parametershowed that reaction exothermic and value of AG is spontaneous. Theadsorption kinetic was found to follow pseudo-second order rate model,due to the high correlation coefficient(R’) and agreement between theexperimental and calculated value of qe (mg/l). The results proved theapplicability of isotherm Freundilch equation for adsorption coefficienthigher than for Langmuir correlation equation.